Association of Beta-2-Microglobulin With Coronary Heart Disease and All-Cause Mortality in the United States General Population - Huang, Yangxi; Lin, Yufeng; Zhai, Xiaobing; Cheng, Long (Frontiers in Cardiovascular Medicine, 2022)
Few prospective studies explored the association of Beta-2-microglobulin (B2M) with coronary heart disease (CHD mortality. The primary objective of the study is to examine the association of serum B2Mwith CHD and all-cause mortality. A prospective cohort study of a nationally representative sample of 4,885 adults, aged 40 to 85, who participated in the National Health and Nutrition Examination Survey (NHANES) III from 1988 to1994. The relationships between B2M and CHD and all-cause mortality were estimated using Cox proportional hazards regression models. During a median follow-up of 15.5 years, 845 CHD and 3388 all-cause deaths occurred among 4,885 participants (2568 women [55.7%]; mean [S.D.] age, 66.4 [12.5] years), respectively. In the unadjusted model, B2M concentration was strongly linearly associated with CHD and all-cause mortality (p-trend < 0.001). After adjusting multivariable factors, a positive linear association between B2M and all-cause mortality was still observed (H.R. for Q4 versus Q1 5.90; 95% CI = 5.31 to 6.57; p-trend < 0.001). In multivariable adjustment model, B2M was significantly associated with an increased risk of CHD mortality (H.R. for Q4 versus Q1 2.72; 95% CI = 2.07 to 3.57; p-trend < 0.001). In the stratified analyses, the associations between B2M with CHD and all-cause mortality did vary by risk factors age, smoking status, and history of hypertension. The findings suggest a significant relationship between the higher serum B2M concentration and increased risk for CHD and all-cause mortality. Further large-scale follow-up studies are also needed to validate this association.